2017
DOI: 10.1016/j.jcrc.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

A nursing perspective of interprofessional work in critical care: Findings from a secondary analysis

Abstract: 3 ABSTRACTPurpose: This paper presents a secondary analysis of nurse interviews from a two-year comparative ethnographic study exploring cultures of collaboration across intensive care units (ICU). Critically ill patients rely on their interprofessional healthcare team to communicate and problem-solve quickly to give patients the best outcome available. Critical care nurses function at the hub of patient care giving them a distinct perspective of how interprofessional interactions impact collaborative practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
3
23
0
3
Order By: Relevance
“…job dissatisfaction, professional burnout, poor communication among colleagues, etc. ), or socio-demographic, educational and occupational characteristics in emergency and critical care nurses (Kendall-Gallagher et al, 2017;Vahedian-Azimi et al, 2019). Previous studies in ED nurses have shown that the majority of those who were bullied reported decreased productivity and declined ability to respond to cognitive demands, as well as to provide support, effective communication and safe care (Al-Ghabeesh and Qattom, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…job dissatisfaction, professional burnout, poor communication among colleagues, etc. ), or socio-demographic, educational and occupational characteristics in emergency and critical care nurses (Kendall-Gallagher et al, 2017;Vahedian-Azimi et al, 2019). Previous studies in ED nurses have shown that the majority of those who were bullied reported decreased productivity and declined ability to respond to cognitive demands, as well as to provide support, effective communication and safe care (Al-Ghabeesh and Qattom, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This hospital service has mainly medical and nursing professionals, for the advanced treatment and to support people in life risk 4,5 . Speech-language therapy has been incorporated in the swallowing therapy [6][7][8] , linguistic-communicative therapy 9,10 and cognitive therapy 11,12 of critical patients, developing a role specifically as a rehabilitator in this context 13 .…”
Section: Introductionmentioning
confidence: 99%
“…La dotación médica (6) y de enfermería (11) cumplen un rol central en el manejo del usuario con riesgo vital y el apoyo de otras profesiones de la salud puede contribuir al proceso de alta de los usuarios y complejiza la provisión del servicio (6,12) . El hecho de que un paciente requiera de más días de hospitalización implica un mayor gasto por parte de los centros hospitalarios (13) y se vuelve relevante valorar los costos asociados a la mantención de un paciente hospitalizado en una UPC, examinando de forma paralela el ujo intrahospitalario, en lo concerniente a servicio de procedencia y tipo de diagnóstico.…”
Section: Introductionunclassified